2021
DOI: 10.2196/28628
|View full text |Cite
|
Sign up to set email alerts
|

Users’ Perceptions Toward mHealth Technologies for Health and Well-being Monitoring in Pregnancy Care: Qualitative Interview Study

Abstract: Background Mobile health (mHealth) technologies, such as wearable sensors, smart health devices, and mobile apps, that are capable of supporting pregnancy care are emerging. Although mHealth could be used to facilitate the tracking of health changes during pregnancy, challenges remain in data collection compliance and technology engagement among pregnant women. Understanding the interests, preferences, and requirements of pregnant women and those of clinicians is needed when designing and introduci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(47 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…It was important to address these issues, especially as they relate to new-born health and safety. For this reason, several studies in the literature were conducted to understand clinicians’ and pregnant women’s perceptions of the potential benefits of mHealth in general and wearable technologies in particular [ 52 , 53 , 54 , 55 ]. Despite not currently using wearable devices in their medical practice, clinicians perceived the benefits of mHealth in supporting antenatal care [ 52 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was important to address these issues, especially as they relate to new-born health and safety. For this reason, several studies in the literature were conducted to understand clinicians’ and pregnant women’s perceptions of the potential benefits of mHealth in general and wearable technologies in particular [ 52 , 53 , 54 , 55 ]. Despite not currently using wearable devices in their medical practice, clinicians perceived the benefits of mHealth in supporting antenatal care [ 52 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, several studies in the literature were conducted to understand clinicians’ and pregnant women’s perceptions of the potential benefits of mHealth in general and wearable technologies in particular [ 52 , 53 , 54 , 55 ]. Despite not currently using wearable devices in their medical practice, clinicians perceived the benefits of mHealth in supporting antenatal care [ 52 , 54 ]. It was also found that pregnant women were open to wearing wearables and using health monitoring devices, but were more likely to use them if clinicians were monitoring their data [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the sample was small, the study represented a group of HIV experts with a wide range of experience. Expert interviews are a suitable instrument for eliciting requirements at an early stage of development, as numerous other studies have shown in the past [68][69][70]. This method allows an intensive exchange with a small group of participants and produces more convincing data than quantitative studies do [71,72].…”
Section: Discussion Of Methodsmentioning
confidence: 99%
“…The openness toward the use of wearable devices in maternal care is mixed [ 15 , 16 ]. Motivation to use wearable devices increases if the use is associated with positive outcomes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%